Purification of surfactin compounds produced by a Bacillus subtilis strain - Bartal, Attila; Hunkár, Henriett; Endre, Gábor; Vörös, Mónika; Vágvölgyi, Csaba; Szekeres, András (Acta Biologica Szegediensis, 2021)
Surfactins are lipopeptide-type biosurfactants produced mainly by Bacillus species containing a peptide loop of seven amino acids and a hydrophobic fatty acid chain. These molecules exhibit various biological activities; therefore, their therapeutic and environmental applications are in the focus worldwide. In our work, a multi-step purification and separation process was developed to isolate surfactins from the ferment broth of B. subtilis SZMC 6179J strain. The process incorporates normal phase flash chromatography for pre-purifying the crude extract and two consecutive reverse phase HPLC separations for the isolation of the various surfactin molecules. The determination of the relative amounts of lipopeptides both in the crude extract and in each fraction of every separation step were carried out by HPLC-HESI-MS examinations. The ratio of surfactins in the crude extract was 21.35%, but after the preparative flash chromatographic separation the relative amount of surfactins was observed to be 30.44%. The preparative HPLC purification step resulted 85.39% purity of the surfactins. Nine different surfactin variants were isolated and identified from the fractions of this final semi-preparative HPLC purification, out of which three compounds were completely purified, and three others were detected in relative amounts of more than 95% in some fractions.